Palm Oil Fresh Fruit Bunch Supply Chain in Bengkulu Province: A Study on Trust Levels Among Suppliers - Romdhon, Muhamad Mustopa; Windirah, Nola; Trisusilo, Agung (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Low mutual trust among suppliers is a significant factor leading to the breakdown of partnerships in the supply chain (Stefani & Sunardi, 2014). This lack of trust can greatly impact the performance and efficiency of the Fresh Fruit Bunch (FFB) supply chain. This study aims to assess the level of trust among suppliers in the FFB supply chain in Bengkulu Province. The trust level among FFB suppliers in Bengkulu Province is evaluated based on three dimensions: ability, benevolence, and integrity. These dimensions are measured using a Likert scale to calculate a trust index. The findings indicate that the trust level among suppliers in the FFB supply chain is high (trust index 89.69%). The study identifies certain indicators that could potentially weaken trust, including competency and experience indicators in the ability dimension, empathy and acceptance indicators in the benevolence dimension, and relevance and reliability indicators in the integrity dimension. To address these potential trust-weakening indicators, a collaborative effort involving independent farmers, suppliers, and mills is recommended.